The Federal Democratic Republic of Ethiopia : Enhanced Initiative for Heavily Indebted Poor Countries-Completion Point Document. (IMF Staff Country Reports; Country Report ;, 2004)
This paper assesses Ethiopia's economic progress under the Enhanced Initiative for Heavily Indebted Poor Countries (HIPC) Initiative, and seeks approval of the IMF staff for the completion point under the initiative. It reviews the status of creditor participation, the delivery of debt relief to Ethiopia, updates the debt sustainability analysis, and provides an analysis of the sensitivity of the debt indicators to changes in macroeconomic variables. Executive Directors determine that Ethiopia has reached the completion point under the Enhanced HIPC Initiative.